Perioperative Strategies to Prevent Surgical-Site Infection - Poggio, Juan Lucas (Clinics in Colon and Rectal Surgery, 2013)
Colon and rectal resections are among the most common surgical procedures performed in the United States. Complication rates of up to 25% have been reported and result in a substantial impact on quality of life and cost of care. Recently, the Surgical Care Improvement Program (SCIP) has promoted guidelines to prevent postoperative and potentially preventable complications. A comprehensive evidenced-based review of these guidelines and other perioperative strategies for practicing colorectal surgeons is the basis of this review.
Keywords: surgical-site infection; colon and rectal surgery; infection control